2002
DOI: 10.1007/s00134-002-1251-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical incidents related to invasive mechanical ventilation in the ICU: preliminary descriptive study

Abstract: Use of our reporting method to create a CI database in a multicenter study including ICUs with varying recruitment patterns may help to identify markers suitable for routine continuous use as part of a quality-assurance program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The CVC rate may be dependent on the definition of CVC, particularly the level and duration of hypotension. Based on previous studies, we arbitrarily defined CVC as an arterial systolic blood pressure ≤65 mmHg recorded at least once and/or ≤90 mmHg lasting ≥30 minutes despite vascular loading with 500–1000 mL of crystalloid and/or colloid solutions and/or necessitating introduction of vasoactive drugs [ 1 , 18 , 19 ]. Mortality in the ICU was not related to hypotension after intubation, regardless of its definition and severity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CVC rate may be dependent on the definition of CVC, particularly the level and duration of hypotension. Based on previous studies, we arbitrarily defined CVC as an arterial systolic blood pressure ≤65 mmHg recorded at least once and/or ≤90 mmHg lasting ≥30 minutes despite vascular loading with 500–1000 mL of crystalloid and/or colloid solutions and/or necessitating introduction of vasoactive drugs [ 1 , 18 , 19 ]. Mortality in the ICU was not related to hypotension after intubation, regardless of its definition and severity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when invasive ventilation is initiated to manage acute respiratory failure, the underlying lung disease (i.e., limited alveolar volume and enhanced shunt fraction) limits per se the efficiency of preoxygenation. As a result, hemoglobin desaturation is a well-known complication in this population (2,4,8,20,23,24). In our study, the incidence of oxyhemoglobin desaturation below 80% was observed in 14 among 53 studied patients (Figure 4).…”
Section: Preoxygenation In Critically Ill Patientsmentioning
confidence: 99%
“…Mechanical ventilation has been associated with adverse events in 69% of ventilated patients. 24 Pneumothorax as a consequence of barotrauma or as a complication from a procedure occurs in 1.5% of patients in the ICU and has been associated with an increased risk of death. 25 Likewise, the support devices required in the care of patients in the ICU can be dislodged causing harm.…”
Section: Event Detectionmentioning
confidence: 99%